Isolation of Cellular Clones of Murine Melanoma Resistants to the Photodynamic Therapy and Characterization of Some Mechanisms Involved in the Radioresistance - E., Ramón-Gallegos; L., Rosas-Flores; C.C., Barrera-Mendoza; Z., Herrera-Carrillo; G., González-Agüero; G., Estrada-Manrique; A., Cruz-Orea (IntechOpen, 2011)
None